The effect of ego depletion on sprint start reaction time - Englert, Christoph; Bertrams, Alex (Journal of sport & exercise psychology, 2014)
In the current study, we consider that optimal sprint start performance requires the self-control of responses. Therefore, start performance should depend on athletes’ self-control strength. We assumed that momentary depletion of self-control strength (ego depletion) would either speed up or slow down the initiation of a sprint start, where an initiation that was sped up would carry the increased risk of a false start. Applying a mixed between- (depletion vs. nondepletion) and within- (before vs. after manipulation of depletion) subjects design, we tested the start reaction times of 37 sport students. We found that participants’ start reaction times decelerated after finishing a depleting task, whereas it remained constant in the nondepletion condition. These results indicate that sprint start performance can be impaired by unrelated preceding actions that lower momentary self-control strength. We discuss practical implications in terms of optimizing sprint starts and related overall sprint performance.
Gesehen am 16.07.2020